Drug utilization study-pattern of use of anti-microbial drugs among post operative patients in department of general surgery at a tertiary care hospital - Patel, Dhwani J.; Chhaiya, Sunita B.; Mehta, Dimple S. (International Journal of Basic & Clinical Pharmacology, 2017)
Background: The objective of this study was to assess the current trends of prescribing antibiotics amongst the patients of General surgery postoperative unit of C. U. Shah Medical College and Hospital, Surendranagar, Gujarat. Methods: An observational study was done amongst 200 patients admitted in the General surgery postoperative ward of a C. U. Shah Medical College and Hospital, Surendranagar over a period of 6 months in accordance with the ethical principles of the ethics committee guidelines. Data were analyzed using Microsoft Office Excel 2007 and values were presented descriptively in percentiles. Results: The average number of antimicrobials per encounter was 1.78. The most common surgeries in the postsurgical unit were urological procedures 61 (30.35%) followed by incision and drainage 40 (20%). Most of the patients were in the age group of 35-60 yrs. Higher utilization of cephalosporins (62.91%) and fluoroquinolones (20.27%). The most preferred route of administration of antibiotics in post operative period was oral (55.58%). Conclusions: The present study provides valuable insight about the overall pattern of anti-microbials used in postoperative patients in a tertiary care hospital. It is intended to be a step in broader evaluation of safety and efficacy of drug as well as for improving prescribing habits among the fraternity and minimizing incidence of resistance to antimicrobials in surgical wards of a teaching hospital.